Effects of bullying on the psychological and mental wellbeing of adolescents in selected secondary schools in Ibadan, Nigeria. (2023)
Bullying is a complex and stressful experience that significantly impacts the psychological and mental well-being of adolescents. While its effects were often overlooked, recent attention from researchers, mental health professionals, social workers, and policymakers has focused on understanding how bullying influences adolescent mental health. This study used a descriptive survey design with a correlation approach to examine the impact of bullying on the psychological and mental well-being of adolescents. A sample of 280 students from tour secondary schools in Ibadan Metropolis (two public, two private) was selected using simple random sampling. Data collection utilized a mix of standardized and self-developed 'Instruments, focusing on bullying experiences and both short- and long-term psychological effects. Statistical analysis, including frequency counts and percentages for demographic data, and Pearson Product Moment Correlation (PPMC) for testing hypotheses at a 0.05 alpha level, was employed. The study revealed that all six short-term psychological variables—anxiety and fear (r = .114), anger and rage (r = .377), humiliation and shame (r = .308), sadness and loneliness (r = .499), self-harm/harm to others (r = .159), and school avoidance/absenteeism (r = .184)—showed significant correlations with bullying. Long-term effects such as erosion of self-esteem and confidence (r= .368). Post-traumatic stress disorder (r = .716), anxiety and depression (r= .278), self- destruction (r = .420), schizophrenia (r = .270), substance abuse (r = .255), and agoraphobia (r - .299) also had significant relationships with bullying among victims in these schools. The findings indicate a significant correlation between bullying and the mental well-being of adolescents, with r(298) = .372, p < 0.05. Additionally, psychological effects (r = .290, p < 0.05) were significantly related to mental well-being. The study concludes that bullying has both short-term and long-term adverse effects on the psychological and mental well-being of adolescents in selected secondary schools in Ibadan. It suggests that parents, teachers, school administrators, counselors, and social workers should be vigilant in identifying these effects to mitigate their impact on the mental health of adolescents.